The association between injuries and overtime play in National Collegiate Athletic Association Soccer - Wasserman, E. B.; Morris, S. N.; Quetant, S. L.; Collins, C. L. (Journal of Athletic Training, 2019)
Context: Unlike most professional soccer leagues, National Collegiate Athletic Association (NCAA) soccer regular season games tied at the end of regulation proceed to two 10-minute sudden victory overtime (OT) periods. Given the extra activity time, OT play may be associated with increased risk of injury. The purpose of this study was to examine the association between injury rates and OT play. Methods: As part of the NCAA Injury Surveillance Program, athletic trainers (ATs) reported injuries requiring medical attention from 2,710 NCAA men`s and 4,356 NCAA women`s soccer games during the 2009/10 through 2016/17 academic years. Using data from the NCAA statistics department, we determined which games went to OT and the number of OTs played. We calculated injury rates per 1,000 minutes played and 95% Confi dence Intervals (CI) by game segment (fi rst half vs. second half vs. OT). Incident Rate Ratios (IRRs) compared injury rates. The minutes played in the first and second halves were the length of the half (45 minutes) multiplied by the number of players on the fi eld (11). For games played from 2014/15-2016/17, the NCAA statistics department provided the length of OT, and this was multiplied by 11 players on the fi eld. For games played from 2009/10-2013/14, if a game went two OTs but ended in a tie, the OT length was 20 minutes; if there were two OTs but did not end in a tie, we assumed 15 minutes of OT play; if there was one OT, we assumed 5 minutes of OT play. Analyses assumed no red cards (i.e., 11 players on the fi eld at all times). Results: In men`s soccer, 447 (16%) games went to OT: 134 (30% of OT games) fi nished in the first OT, and 313 (70% of OT games) had two OTs. In women`s soccer, 772 (18%) went to OT: 214 (28% of OT games) fi nished in the first OT, and 558 (72% of OT games) had two OTs. In both men`s and women`s soccer, injury rates were highest in the second half (Table 1). Injury rates were signifi cantly higher in the second half compared to the fi rst half (men`s IRR=1.65, 95%CI:1.43-1.89; women`s IRR=1.42, 95%CI:1.27-1.59); however, rates were not signifi cantly different between overtime and either half of play (men`s OT vs. fi rst half IRR=1.25, 95%CI:0.80-1.94; men`s OT vs. second half IRR=0.76, 95%CI:0.49-1.17; women`s OT vs. fi rst half IRR=1.03, 95%CI:0.73-1.45; women`s OT vs. second half IRR=0.72, 95%CI:0.51-1.02). Conclusions: The injury rate was no higher in overtime than either of the halves, meaning injuries are not more likely to occur during overtime; however, we can expect more injuries in a game that has overtime than one that does not because the players are on the field for more time.